Si/SiGe superlattice I/O finFETs in a vertically-stacked Gate-All-Around horizontal Nanowire Technology - Hellings, G.; Mertens, H.; Subirats, A.; Simoen, E.; Schram, T.; Ragnarsson, L.-A.; Simicic, M.; Chen, S.-H.; Parvais, B.; Boudier, D.; Cretu, B.; Machillot, J.; et al. (2018 IEEE Symposium on VLSI Technology, 2018)
This work presents Si/SiGe superlattice finFETs (FF) for 1.8V/2.5V I/O applications in vertically-stacked Gate-All-Around horizontal nanowire technology (hNW) technology. Superlattice FF have a higher ION than I/O hNW reference devices and can be more easily integrated into a GAA hNW technology than Si I/O FF. These novel I/O FET structures exhibit competitive analog performance and are superior as ESD protection devices.